Effect of Build Parameters on the Mechanical Behavior of Polymeric Materials Produced by Multijet Fusion. Issue 9 (13th January 2022) - Chen, Andrew Y.; Chen, Ailin; Wright, Jake; Fitzhugh, Andrew; Hartman, Aja; Zeng, Jun; Gu, Grace X.
Abstract : Multijet fusion (MJF) is a novel additive manufacturing (AM) process for the powder bed fusion of thermoplastic polymers. In recent years, MJF has been established as a promising manufacturing technique for the rapid prototyping and production of fully functional, large‐scale components at high resolution. Like other powder bed fusion techniques, MJF permits the printing of parts without support material, and does not require chemical postprocessing steps, making it especially suitable for fabricating parts with complex and intricate internal features. However, the effects of common build volume parameters (such as part orientation, location, and interpart spacing) on mechanical properties are currently not well understood. This study aims to provide a thorough and comprehensive description of the trends in mechanical properties observed in polyamide (PA)‐11 and PA‐12 samples printed using the MJF process. Tensile, flexural, and impact specimens are printed using varying build volume packing parameters and tested according to the corresponding ASTM standards. The fracture surfaces of tested specimens are studied and characterized to further understand the method of failure propagation through MJF‐printed PA‐11 and PA‐12. As this work demonstrates, determining an optimal bed packing algorithm will be instrumental for optimizing desired mechanical properties of printed parts. Abstract : Multijet fusion (MJF) is a promising novel power‐based additive manufacturing process for polymeric materials. This study performs a thorough characterization of the tensile, flexural, and impact properties of MJF‐printed polyamide‐11 and polyamide‐12 as a function of build parameters. Strength, stiffness, elongation at break, and energy absorption are studied as part orientation, location, and specimen size are varied.